Case report: A novel de novo deletion mutation of DYRK1A is associated with intellectual developmental disorder, autosomal dominant 7 - Zhou, Cong; Zhu, Hongmei; Xiang, Qinqin; Mai, Jingqun; Wang, Xihan; Wang, Jing; Liu, Shanling (Frontiers in Neuroscience, 2023)
Background: Intellectual developmental disorder 7 (IDD7) is an autosomal dominant disease. The main clinical features of IDD7 include intellectual disability, microcephaly, and developmental delay. This study aimed to identify pathogenic variants in a Chinese girl with developmental delay, impaired social interaction, and attention deficit hyperactivity disorder. Case presentation: The case was a 6-year-old girl. Clinical symptoms of the patient mainly included developmental delay, seizures, attention deficit hyperactivity disorder, and impaired social interaction. The patient presented with microcephaly, bushy eyebrows, a short lingual frenum, binocular esotropia, bilateral valgus and external rotation, and walked with an abnormal gait. Using whole-exome sequencing, we identified a 9,424 bp de novo heterozygous deletion (containing coding exons 10, 11, and 12, and partial sequences of non-coding exon 12) in DYRK1A, which is responsible for IDD7. The DYRK1A variant is classified as pathogenic according to the criteria of the American College of Medical Genetics and Genomics (ACMG). Conclusions: The findings of this study augment the data regarding the pathogenic variants of DYRK1A and provide important information for molecular diagnosis.